2018
DOI: 10.1371/journal.pone.0194392
|View full text |Cite
|
Sign up to set email alerts
|

Severe influenza A(H1N1)pdm09 in pregnant women and neonatal outcomes, State of Sao Paulo, Brazil, 2009

Abstract: To investigate the factors associated with death and describe the gestational outcomes in pregnant women with influenza A(H1N1)pdm09, we conducted a case-control study (deaths and recovered) in hospitalized pregnant women with laboratory-confirmed influenza A(H1N1)pdm09 with severe acute respiratory illness (SARI) in the state of São Paulo from June 9 to December 1, 2009. All cases were evaluated, and four controls that were matched by the epidemiological week of hospitalization of the case were randomly selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…Prior studies have indicated that pregnant women are considered a high‐risk population for influenza A(H1N1) pdm09 and avian influenza viruses and are more likely to develop severe complications and to die, especially when infection occurs in the middle and late trimesters . The case‐patient, a 36‐week pregnant woman was exposed to sick chickens and was infected with the avian influenza A(H5N1) virus, developed rapid progressive severe pneumonia, lymphopenia, sever hypoxia and increased aminotransferase levels, similar to previously reported avian influenza A(H5N1) patients Common complications of highly pathogenic avian influenza (HPAI) H5N1 virus infection such as primary pneumonia, respiratory failure due to ARDS, and fatal outcome have been seen and recorded in the case‐patient's clinical progress .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Prior studies have indicated that pregnant women are considered a high‐risk population for influenza A(H1N1) pdm09 and avian influenza viruses and are more likely to develop severe complications and to die, especially when infection occurs in the middle and late trimesters . The case‐patient, a 36‐week pregnant woman was exposed to sick chickens and was infected with the avian influenza A(H5N1) virus, developed rapid progressive severe pneumonia, lymphopenia, sever hypoxia and increased aminotransferase levels, similar to previously reported avian influenza A(H5N1) patients Common complications of highly pathogenic avian influenza (HPAI) H5N1 virus infection such as primary pneumonia, respiratory failure due to ARDS, and fatal outcome have been seen and recorded in the case‐patient's clinical progress .…”
Section: Discussionsupporting
confidence: 74%
“…The case‐patient received an initial presumptive dose of oseltamivir for 5 days after the onset of illness and before influenza infection was confirmed; however, the WHO technical guidelines recommends that patients with suspected influenza should receive oseltamivir as early as possible to reduce mortality . Findings by Riberio et al indicated that antiviral treatment was a protective factor to the A(H5N1) virus when administered within 48 hours of the onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Some evidence showed that early antiviral treatment within 72 hours of disease onset is beneficial. 26 Obesity is another risk factor for severity, hospitalization, and mortality for influenza and BMI is positively associated with the likelihood of hospitalization. [27][28][29] In addition to that, obese patients are more likely to develop secondary bacterial infection.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Infants born to mothers who were vaccinated against influenza may have a decreased rate of preterm birth, low birthweight, and stillborn birth, although establishing a causal relationship is challenging [160,[166][167][168][169][170][171]. Infants born to mothers who were severely sick with H1N1 influenza infection have been shown to have an increased risk of preterm birth, decreased 5 min Apgar scores, and an increased risk of death [172][173][174]. These data support vaccinating pregnant women to help improve the health of both the mother and child.…”
Section: A Key Role For Maternal Vaccination In Protecting Young Infamentioning
confidence: 99%